Deactivation of Mn/TiO2 catalyst for NH3-SCR reaction: effect of phosphorous. Issue 14 (27th January 2016) - Yang, Ning-zhi; Guo, Rui-tang; Wang, Qing-shan; Pan, Wei-guo; Chen, Qi-lin; Lu, Chen-zi; Wang, Shu-xian
Abstract : The deactivation mechanism of phosphorous on a Mn/TiO2 catalyst for selective catalytic reduction of NO with NH3 was investigated in this study. Abstract : The deactivation mechanism of phosphorous on a Mn/TiO2 catalyst for selective catalytic reduction of NO with NH3 was investigated in this study. It was found that the NH3 -SCR reaction over the Mn/TiO2 catalyst obeyed the Langmuir–Hinshelwood mechanism. From the characterization results, it could be found the addition of phosphorous on the Mn/TiO2 catalyst would decrease its reducibility and inhibit the adsorption of chemisorbed oxygen and NO x species on its surface. As a result, the P-doped Mn/TiO2 catalyst was deactivated.